Defective expansion and function of memory like natural killer cells in HIV+ individuals with latent tuberculosis infection. - Kamakshi Prudhula Devalraju (Public Library of Science (PLoS), 2021)
Purpose Tuberculosis (TB) is the leading cause of infectious disease related mortality, and only 10% of the infected individuals develop active disease. The likelihood of progression of latent tuberculosis infection (LTBI) to active TB disease is high in HIV infected individuals. Identification of HIV+ individuals at risk would allow treating targeted population, facilitating completion of therapy for LTBI and prevention of TB development. NK cells have an important role in T cell independent immunity against TB, but the exact role of NK cell subsets in LTBI and HIV is not well characterized. Methods In this study, we compared the expansion and function of memory like NK cells from HIV-LTBI+ individuals and treatment naïve HIV+LTBI+ patients in response to Mtb antigens ESAT-6 and CFP-10. Results In freshly isolated PBMCs, percentages of CD3-CD56+ NK cells were similar in HIV+LTBI+ patients and healthy HIV-LTBI+ individuals. However, percentages of CD3-CD56+CD16+ NK cells were higher in healthy HIV-LTBI+ individuals compared to HIV+LTBI+ patients. HIV infection also inhibited the expansion of memory like NK cells, production of IL-32α, IL-15 and IFN-γ in response to Mtb antigens in LTBI+ individuals. Conclusion We studied phenotypic, functional subsets and activation of memory like-NK cells during HIV infection and LTBI. We observed that HIV+LTBI+ patients demonstrated suboptimal NK cell and monocyte interactions in response to Mtb, leading to reduced IL-15, IFN-γ and granzyme B and increased CCL5 production. Our study highlights the effect of HIV and LTBI on modulation of NK cell activity to understand their role in development of interventions to prevent progression to TB in high risk individuals.